Harnessing the pillars of institutions to drive environmentally sustainable hospital foodservices - Carino, Stefanie; Collins, Jorja; Malekpour, Shirin; Porter, Judi (Frontiers in Nutrition, 2022)
Background: The cultural-cognitive, normative and regulative pillars of institutions influence the ability of hospitals to change how they function at an organizational and operational level. As more hospitals and their foodservices instigate changes to address their environmental footprint and impact on food systems, they move through the “sustainability phase model” from no response through to high level action and leadership. The aim of this study was to describe and compare the pillars of institutions between hospitals in different stages of achieving environmentally sustainable foodservices (business-as-usual vs exemplar hospitals). Methods: For this qualitative inquiry study, interviews were conducted with 33 hospital staff from 3 business-as-usual hospitals in Melbourne, Australia and 21 hospital staff from 14 exemplar hospitals across 9 countries. Participants were asked questions about their perspectives on environmental sustainability in foodservices and the barriers, enablers and drivers they experienced. Each data set was analyzed thematically and then compared. Findings: There was a clear and distinct difference in responses and behaviors within each pillar between the exemplar and business-as-usual hospitals. The cultural-cognitive pillar identified a similarity in personal belief in the importance of addressing environmental impacts of foodservices, but difference in how staff saw and acted on their responsibility to drive change. The normative pillar uncovered a supportive culture that encouraged change in exemplar hospitals whilst business-as-usual hospital staff felt disheartened by the difficult processes and lack of support. The regulative pillar reflected business-as-usual hospital staff feeling restricted by government policy versus exemplar hospital participants who were motivated to internalize government policy in different ways and work with other hospitals to advocate for better policy. Interpretation: These findings highlight strategies related to each of the three pillars of institutions that can be used to drive effective, sustainable long term change within hospitals. This includes staff education and training, revisiting hospital culture and values around environmental sustainability, embedding sustainable foodservices in internal policies, and a comprehensive government policy approach to sustainable healthcare.